Standardized subxiphoid echocardiography in swine: procedural guide and reference values - Billig, Sebastian; Derwall, Matthias; Uhlig, Moritz; Zayat, Rachad; Yelenski, Sergej (Frontiers in Cardiovascular Medicine, 2025)
BackgroundSubxiphoid echocardiography (SE) via small surgical access offers a minimally invasive imaging technique for preclinical swine models. However, a detailed methodological description that includes the surgical approach and imaging planes is lacking. The aim of this study was to standardize SE performed via a subxiphoid surgical approach and to provide reference values for future research.MethodsSE was performed in 19 female German Landrace pigs under general anesthesia using a defined imaging protocol. After the induction of general anesthesia, a small subxiphoid incision was made to optimize the image quality for SE. The echocardiographic imaging protocol was adapted from human 2D-transthoracic echocardiography and included apical 2-, 3-, and 5-chamber views and Doppler measurements of blood flow and tissue velocities. Furthermore, speckle tracking was used to assess left ventricular (LV) and right ventricular (RV) myocardial deformation.ResultsDuring SE, the animals were under stable anesthesia with a heart rate of 65 ± 12 beats per minute, and a mean arterial pressure of 88 ± 12 mmHg. Blood gas values were within physiological ranges. High-quality images of both ventricles were consistently achieved using the established imaging protocol. One animal showed a severe aortic stenosis and was excluded from the analysis. The biplane LV stroke volume was 45 ± 13 ml and the LV ejection fraction was 67% ± 11%. LV-global longitudinal strain (GLS) was −22.4% ± 3.3%, and RV free wall longitudinal strain was −23.7% ± 5%. The Vmax of the aortic valve was 1.6 ± 0.3 m/s.ConclusionSE offers a standardized and reproducible imaging technique for the assessment of high-quality apical views in swine models. This study provides procedural guidance and reference values for translational research applications.